Crystal structure of 4-bromobenzyl 2-(6-methoxy-naphthalen-2-yl)propanoate, C21H19BrO3 - Zhang Xin-Ru; Lin Da-Zhuan; Gao Li-Na (Zeitschrift für Kristallographie - New Crystal Structures)
C21H19BrO3, orthorhombic, P212121 (no. 19), a = 6.011(2) Å, b = 11.630(2) Å, c = 25.165(5) Å, V = 1759.3(7) Å3, Z = 4, Rgt (F) = 0.0163, wRref (F 2) = 0.0420, T = 100(2) K.